Caffeic Acid Protects against Iron-Induced Cardiotoxicity by Suppressing Angiotensin-Converting Enzyme Activity and Modulating Lipid Spectrum, Gluconeogenesis and Nucleotide Hydrolyzing Enzyme Activities - Salau, Veronica F.; Erukainure, Ochuko L.; Islam, Md. Shahidul (Biological trace element research, 2021)
The protective effects of caffeic acid on angiotensin-converting enzyme (ACE) and purinergic enzyme activities, as well as gluconeogenesis was investigated in iron-induced cardiotoxicity. Cardiotoxicity was induced in heart tissues harvested from healthy male SD rats by 0.1 mM FeSO 4 . Treatment was carried out by co-incubating hearts tissues with caffeic acid and 0.1 mM FeSO 4 . Cardiotoxicity induction significantly ( p < 0.05) depleted GSH level, SOD, catalase, and ENTPDase activities, with concomitant elevation of the levels of malondialdehyde (MDA), nitric oxide, ACE, ATPase, glycogen phosphorylase, glucose 6-phosphatase, fructose 6-biphsophatase, and lipase activities. There was significant ( p < 0.05) reversion in these levels and activities on treatment with caffeic acid. Caffeic acid also caused depletion in cardiac levels of cholesterol, triglyceride, LDL-c, while elevating HDL-c level. Our results suggest the protective effect of caffeic acid against iron-mediated cardiotoxicity as indicated by its ability to suppress oxidative imbalance and ACE activity, while concomitantly modulating nucleotide hydrolysis and metabolic switch.